A Comprehensive Review on the Management of Ulcerative Colitis: From Global Epidemiology to Personalized Therapeutics (Bangladesh Journal of Medicine, 2026)
Ulcerative colitis (UC) is a chronic, immune-mediated inflammatory disease of the colonic mucosa, characterized by a relapsing and remitting course. Once considered a disease of the Western world, its incidence and prevalence are rising rapidly in Asia, including Bangladesh, creating a significant healthcare burden. The clinical presentation is heterogeneous, ranging from mild distal disease to lifethreatening acute severe colitis, often accompanied by debilitating extra-intestinal manifestations. Diagnosis is multifaceted, relying on clinical suspicion, confirmed by endoscopic and histological evidence of chronic colitis, after the exclusion of infectious mimics. The management paradigm has shifted profoundly from symptomatic control to a proactive “treat-to-target” (T2T) strategy, with the goal of achieving sustained deep remission (clinical and endoscopic). This evolution has been fueled by an expanding therapeutic armamentarium, including a growing number of biologic therapies targeting specific immune pathways and novel small molecule drugs. This review provides a detailed, contemporary overview of UC, with a special focus on the changing epidemiology in Asia, the intricacies of medical and surgical management. The future of UC care lies in truly personalized medicine, guided by predictive biomarkers and a shared decision-making model.Bangladesh J Medicine 2026; 37(1): 3-9